A Study on Menstruation and Personal Hygiene Among Adolescent Girls of Government Medical College, Solapur - Kendre, Varsharani V; Ghattergi, Chandrashekhar H (National Journal of Community Medicine, 2013)
Introduction: Menstruation is fundamental phenomenon among adolescent girls. It is essential to emphasize on problems of menstruation and personal hygiene during this period. Purpose: 1) To study menstruation and problems of menstruation of adolescent girls of Urban Health Center, Govt. Medical College Solapur.2) To study personal hygiene of adolescent girls of Urban Health Center, Govt. Medical College Solapur. Methodology: A community based cross-sectional study was done involving 246 adolescent girls (116 nonslum and130 slum) of Urban Health Center, Solapur. By doing house to house survey, adolescent girls were interviewed with the help of predesigned, pretested questionnaire. Their personal hygiene was assessed and detail menstrual history was taken. Results: Among nonslum girls, 75.86% had attained menarche and among slum girls, 73.85% had attained menarche. The mean age of menarche in nonslum girls (13.01± 0.71) was significantly less than slum girls (13.33± 0.76).Most of the girls had regular menstrual cycle; duration was 3 to 5 days and moderate blood flow. Very less number of slum girls used sanitary pads during menses as compared to nonslum girls. Dysmenorrhoea was common gynecological problem in both areas. Good personal hygiene was seen in very less slum girls. Conclusions: Dysmenorrhoea was common problem among adolescent girls. The personal hygiene was not good among slum adolescent girls.